Efficiency and safety of microneedling fractional radiofrequency in the treatment of Chinese atrophic acne scars: A retrospective study of 3 consecutive treatments with 1‐month intervals. (2nd December 2022) - Huang, Linting; Liu, Yang; Fang, Wei; Liu, Lanjun; Sun, Qilin; Lin, Xiaoxi; Xu, Hui; Yang, Yali
Abstract: Background: Atrophic acne scars (AAS) impact the aesthetic appearance, inducing social and psychological problems. Effective and safe therapy for AAS is urgently needed now. Microneedling fractional radiofrequency (MFRF) has emerged as a minimal invasive alteration for treating AAS lately, while the existing data on Chinese population was few. Aims: We aimed to explore the effectivity and safety of MFRF in Chinese patients with facial AAS and analyze the response of different subtypes to MFRF treatment. Methods: We conducted a retrospective analysis using data from medical records and clinical photographs of 40 Chinese patients with AAS with Fitzpatrick skin type III‐IV, all of them had received 3 MFRF treatments with 1‐month intervals and were followed up 3 months after the last treatment. The clinical severity was assessed through échelle d'évaluation clinique des cicatrices d'acné (ECCA) score at each visit. Clinical photographs were taken by VISIA. Patients were asked to evaluate their satisfaction of the treatment using a 5‐point Likert scale at the last visit. Results: ECCA score decreased more than a half at the last visit based on the baseline. Among the three types of AAS, the M‐shaped scars respond most quickly to MFRF and the U‐shaped scars improved the most after 3 months follow‐up. A significant improvement was seen in clinical appearance, parallel to the change of ECCA, indicating the remarkable improvement of AAS after the MFRF treatment. Concomitant active acne was controlled along with the improvement of AAS. Statistics from VISIA showed excellent improvement in pores and texture as well. Side effects including pain and erythema were transient and mild. The number of MFRF treatment sessions was positively associated with the degree of improvement. Of the total 39 patients who had given a score of satisfaction, more than 89% (35 patients) were very satisfied or satisfied with the outcome. Conclusions: To sum up, our study reveals that MFRF provides high efficiency in treating Chinese AAS patients with high satisfaction and low risk of adverse effects. M‐shaped scars are the most sensitive type to the treatment, but the U‐shaped scars improve most at the last visit. The simultaneous minimization of pores and improvement of skin texture imply the increased collagen stimulated by MFRF. Regular MFRF should be considered a good choice in treating AAS.